ANALISIS ARUS KAS DAN RASIO LIKUIDITAS PADA KOPERASI UNIT DESA (KUD) KARYA MAJU DESA BERUMBUNG BARU KECAMATAN DAYUN KABUPATEN SIAK - Resty Vinanda Sari; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine and analyze the liquidity of KUD Karya Maju, Berumbung Baru Village in Dayun District of Siak Regerency from 2017 to 2021 using the cash flow ratio and liquidity ratio. Quantitative data are is the type of data used in this study. The data sources used are primary data obtained from interviews and secondary data, namely the financial report data of Village Unit Cooperative Karya Maju, Berumbung Baru Village in Dayun District of Siak Regerency the 2017-2021 period. The data analysis technique used is to calculate cash flow ratios such as the Operating Cash Flow ratio (AKO), Cash Coverage ratio on current liabilities (CKHL), and the capital expenditure ratio (PM), and liquidity ratios such as the current ratio, cash ratio and quick ratio. based on the results of financial data analysis of the Village Unit Cooperative Karya Maju's financial data study, Berumbung Baru Village in Dayun District of Siak Regency, liquidity in 2017 to 2021 in terms of cash flow ratio is in the unfavorable category. The ability of cooperatives to pay their short-term obligations in terms of current ratio is in fairly good condition and in terms of quick ratios they are in very good condition and the ability of cooperatives to provide cash to pay their short-term liabilities is in good condition. Judging from the analysis of cash flow ratio and liquidity ratio, it is said that the liquidity of KUD Karya Maju, Berumbung Baru village, Dayun District, Siak Regency needs to be increased again, in order to get very good results. Keywords: Statement of Cash Flow, Liquidity, Cooperative